The Common Core State Standards Initiative as an Innovation Network. (February 2022) - Rowan, Brian; White, Mark
This article analyzes the Common Core State Standards initiative as an innovation network. Using narrative data and quantitative analysis of hypertext linkages on the World Wide Web, we describe a network of about 3200 organizations that arose to scale up the Common Core State Standards and link them to aligned academic resources such as assessments, instructional materials, and professional development. By 2017, this network developed a "core-periphery" topology. The article describes structures and processes at the core of the network that created strong pressures for construction of a coherent ecosystem of instruction for American education and processes at the periphery that that worked against use of this system by most organizations in the network.